(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The basic purpose of this article is to introduce a generalized version of pseudo-monotone variational inequality in the setting of complete CAT(0) spaces and to present some strong and Δ-convergence results for the existence of solutions for the respective variational inequality problem. Algorithm 1 and 2 are proposed in accordance with pseudo-monotone and α-strongly pseudo-monotone mappings to prove our results under some conditions. A numerical implication of our proposed algorithm is also presented.